IMPLEMENTATION CHALLENGES OF DATA PROTECTION LAW IN NIGERIAN HIGHER EDUCATION - Rosyad, Ali Miftakhu; Adelakun, Najeem Olawale; Amiarsa, Panji; Kamal, Maulana; Hamamah, Fatin (FOCUS: Jurnal of Law, 2025)
This study examines the gap between the existence of data protection regulations and their ineffective implementation in Nigerian higher education institutions. Despite the enactment of the Nigeria Data Protection Regulation (NDPR) 2019 and the Nigeria Data Protection Act (NDPA) 2023, universities continue to face challenges in ensuring data security and compliance. This research explores why implementation remains ineffective and how legal, technological, and organizational factors contribute to this condition. Using a socio-legal approach, the study combines normative legal analysis with empirical data from semi-structured interviews. The findings show that weak enforcement, limited institutional capacity, inadequate ICT infrastructure, low legal awareness, and unsupportive organizational culture hinder effective implementation. These factors interact to create systemic barriers to compliance. The study emphasizes the need for stronger enforcement, institutional reform, capacity-building, and technological investment to achieve effective data protection.